A Case Report on Coronary Artery Perforation During Percutaneous Intervention - Hussain, Asraf; Regmi, Shyam Raj; Dhital, Bishnu Mani; Thapa, Shovit; Thapa, Sagar; Murarka, Rohit; Chaudhary, Ramgobind; Shrestha, Ashok; Shrestha, Roshan; Adhikari, Bishwaraj (Journal of National Heart and Lung Society Nepal, 2022)
Coronary artery perforation (CAP) is one of the most dreadful complications encountered during Percutaneous Coronary Intervention (PCI). Though being rare, the high mortality rate associated with CAP makes it one of the most important complications that should be well known to all the coronary interventionist.The treatment modalities range from balloon tamponade, reversal of anticoagulation, coils, microbeads, pericardiocentesis, covered stents and in desperate situations, coronary artery bypass graft. We present here a case of 65 year old male with extensive anterior wall myocardial infarction who developed CAP of proximal left anterior descending artery during PCI. The case was successfully managed with covered stent.